The Effectiveness of the Child Protection Law in Preventing and Handling Child Violence in the Digital Era - Annisa Yulianti; Clara Devi Srianti (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
The digital era has introduced new forms of child violence, which necessitate an evaluation of Indonesia's Child Protection Law (UU Perlindungan Anak). This study aims to analyze the effectiveness of the Child Protection Law in preventing and addressing child violence in the digital age, with a focus on the roles of government, law enforcement, society, families, and digital platform providers. A key contribution of this research is its holistic approach to the entire spectrum of child violence, thereby bridging the often-separated aspects of conventional law and the dynamics of cybercrime. Utilizing a mixed-methods approach, data were collected through in-depth interviews with stakeholders, focus group discussions, surveys, and document analysis, and subsequently analyzed within the framework of Legal Effectiveness Theory. Findings reveal significant challenges in implementing the Child Protection Law, including slow regulatory adaptation, inadequate law enforcement capacity, low digital literacy, and insufficient proactive commitment from digital platform providers. Case handling, from reporting to victim recovery, faces substantial obstacles, such as jurisdictional complexities and the provision of holistic support. This research has significant social implications for enhancing public awareness and promoting active community participation, while also informing policy reforms and institutional capacity building to foster a safer digital ecosystem for Indonesian children. Recommendations call for responsive legal reforms, strengthened capacities among actors, integrated cross-sector collaboration, and widespread digital literacy.